Nothing to lose - Jance, Judith A. (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Years ago, when he was a homicide detective with the Seattle PD, J. P. Beaumont's partner, Sue Danielson, was murdered. Volatile and angry, Danielson's ex-husband came after her in her home and, with nowhere else to turn, Jared, Sue's teenage son, frantically called Beau for help. As Beau rushed to the scene, he urged Jared to grab his younger brother and flee the house. In the end, Beaumont's plea and Jared's quick action saved the two boys from their father's murderous rage. Now, almost twenty years later, Jared reappears in Beau's life seeking his help once again--his younger brother Chris is missing. Still haunted by the events of that tragic night, Beau doesn't hesitate to take on the case. Following a lead all the way to the wilds of wintertime Alaska, he encounters a tangled web of family secrets in which a killer with nothing to lose is waiting to take another life" --
109583
Keywords: Beaumont, J. P. (Fictitious character) -- Fiction; Police -- Washington (State) -- Seattle; Missing persons -- Investigation; Murder -- Investigation; Family secrets; Private investigators; Seattle (Wash.); Alaska; Suspense fiction; Detective and mystery fiction